Stock assessments of the Black Sea anchovy during the period 1979-1993 - PRODANOV, K.B.; STOYANOVA, M.D. (Mediterranean Marine Science, 2001)
The stock assessments of the Black Sea anchovy during the period 1979-1993 were made by Age- and Length-structured VPA. According to the obtained results, the initial anchovy exploited biomass varied from 1421.3 (1979) to 243.3 thousand tons (1990). In 1979 the mean exploited biomass was 1036.5 thousand tons. Both assessments are very close because the mean biomass at F=0.5 has to be 73.71% from the initial one. The comparatively low level of fishing activity from 1968-1977 (mean value of F was 0.2407) and the increase in Black Sea productivity predetermined the increase in anchovy biomass during the period 1979-1983. This rise in productivity of the Black Sea implies higher values of the anchovy exploited biomass, but this did not occur due to the increased fishing mortality upon the anchovy, which kept its abundance and biomass at considerably lower levels. The mean value of F was 0.7348 during the period 1983-1986 and reached 1.2487 in 1987-1988. The mean anchovy biomass in 1991 and 1992 was 179.1 and 314.0 thousand tons. In the same years the initial anchovy biomass was 430.5 and 592.1 thousand tons. The mean value of the fishing mortality coefficient in 1991 and 1992 was 0.3889 and 0.6353, respectively. Consequently, the decrease of fishing mortality during the specified years was o